Iron Oxide Scale Formation Mechanism and Anti-Corrosion Technology from Induction Remelting of Boiler Coating in Waste Incineration Power Plant - Zuopeng Qu; Xinli Tian (Molecules)
High-frequency induction welding technology represents the development direction of the high-temperature corrosion protection technology for the heating surfaces of the boiler “four tubes”. However, when the high-frequency induction coil heats and remelts the coating on the tube’s outer wall, the tube’s inner wall is also heated, causing an iron oxide scale to form on the tube’s inner wall. When the remelting temperature rises and the temperature of the tube’s inner wall exceeds 580 °C, three layers of oxide films, FeO, Fe3O4, and Fe2O3 are arranged in sequence from the substrate surface of the tube’s inner wall to the outside, with a thickness ratio of approximately 1:10:100. From the XRD spectra of tube iron oxide scale, it can be seen that the oxidation of the tube. The skin is mainly composed of Fe3O4, with a certain amount of Fe2O3 and trace amounts of FeO. The iron in the diffraction peak originates from the metal matrix. However, when the remelting temperature continues to rise and the temperature of the tube’s inner wall exceeds 580 °C, the oxide film begins to thicken significantly, that is, the oxide film begins to transform into an oxide scale. Under the continuous action of high-temperature induction remelting, the reaction between iron and oxygen is accelerated, but because the oxygen ions of water slowly diffuse through two outer layers of oxide films, with a low oxygen concentration. Although the FeO film is thin, it has a loose structure and numerous lattice defects, is unstable and easy to decompose, and easily peels off from the tube’s inner wall. For a pipe wall thickness of 5 mm, if the thinning rate of the inner wall caused by detachment reaches 0.8 mm/year, it is highly likely to cause pipe burst accidents within 4–5 years. The influence of the iron oxide scale on the performance of the tube’s inner wall was evaluated by testing indexes, such as surface hardness and decarburization layer depth. Although the oxide scale reduces the surface hardness of the tube’s inner wall, the surface decarburization layer is very thin, so the effect on the mechanical properties of the tube’s substrate is limited. The technology of inhibiting the formation of the iron oxide scale in induction remelting is briefly introduced. During the high-frequency remelting process of water-cooled walls, as the tube bank moves forward relative to the high-frequency heating coil, nitrogen protection is used to suppress the formation of oxide scale, effectively eliminating the troubles caused by high-frequency induction remelting and achieving the goal of improving the service life of the tube bank. This technology of the nitrogen protection method is used to inhibit the formation of iron oxide scale, not only inhibiting the formation of the iron oxide scale on the tube inner wall and the back of the tube bundle, with remarkable experimental results and broad application prospects.